Design of a power-efficient and high fidelity class-D amplifier - Ye, Jing (2014)
This Final Year Project (FYP) pertains to a mid-power (20W, 20V) analog Class D power amplifier for audio applications. Power amplifier is usually the most power consuming block in an audio system and in some applications, the power consumption of the power amplifier is >70% of the overall power dissipation. Therefore it is imperative that the power-efficiency of the power amplifier be high.